Answer:
B) part
Step-by-step explanation:
Answer:
-1 x - 2
f (x) = -----------
3
Step-by-step explanation:
Then we have y = 3x + 2.
Next, interchange x and y, obtaining x = 3y + 2
Next, solve this result for y: 3y = x - 2; then divide both sides by 3:
y = (x-2)/3
Last, replace "y" with the inverse function label:
-1 x - 2
f (x) = -----------
3
Answer:
$0.50 x 3 = $1.50
Step-by-step explanation:
Answer:
m= -13
Step-by-step explanation:
step1: left part times 26 is m
step2: right part times 26 is -13
so m= -13
Could you maybe add more info? like a story or something